Link prediction and recommendation in signed social networks - Li, Xiaoming (Nanyang Technological University, 2020)
Link prediction is a fundamental research issue in social networks, which aims to infer the formation of a possible link in the near future. This topic is well studied in the last few years as its significant contributions to improve and enhance online experiences, in the form of further facilitating applications such as recommenders for products or friends, trust-aware business applications and viral marketing campaigns. With the rise of signed networks, the link prediction problem becomes more complex and challenging as it introduces negative relations among users. Instead of predicting future relation for a pair of users, however, the current research focuses on distinguishing whether a certain link is positive or negative, on the premise of the link existence. The situation that two users do not have relation (i.e., no-relation) is also not considered, which actually is the most common case in reality.